2016
DOI: 10.1016/j.jcf.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of patients with cystic fibrosis presenting an indeterminate glucose tolerance (INDET)

Abstract: Prospective studies are required to establish if the INDET-CF group can identify clinically relevant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
1
39
0
5
Order By: Relevance
“…It should be noted that our observations also support the recently proposed glucose tolerance category recognized as indeterminate (INDET) which is characterized by elevated G60, but with normal G0 and G120 values [7,30]. In fact, we used the G60 median value as a marker because it targets all glucose tolerance groups, including patients with normal glucose tolerance, impaired glucose tolerance, INDET and CFRD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It should be noted that our observations also support the recently proposed glucose tolerance category recognized as indeterminate (INDET) which is characterized by elevated G60, but with normal G0 and G120 values [7,30]. In fact, we used the G60 median value as a marker because it targets all glucose tolerance groups, including patients with normal glucose tolerance, impaired glucose tolerance, INDET and CFRD.…”
Section: Discussionsupporting
confidence: 80%
“…Since CF patients present a specific OGTT pattern characterized by early glucose excursions with rapid normalization as well as major defects in early insulin secretion, OGTT intermediate time points rather than fasting and 2-h values could provide more pertinent information in identifying an association between glucose and/or insulin and clinical deterioration [5,28,29]. The prevalence of glucose abnormalities identified with the OGTT is important in children (23 to 44 %) as well as in adults (around 60 %) [30,31]. Several studies have used the OGTT to investigate the relationship between glucose abnormality and insulin secretion/sensitivity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a single or even a few CGM-glucose values ≥11.1 mmol/L does not necessary represent a diabetes diagnosis, but probably better reflect the importance of a high glycemic excursion which is present in most CF patients. As such, glucose excursions are more frequent in adult patients [6], and the reported OGTT sensitivity by Mainguy et al could have been even lower in older patients.…”
Section: To the Editormentioning
confidence: 93%
“…These studies conducted on small groups of patients reported that one-third of the patients with normal OGTT present CGM glucose excursions above the usual threshold used to diagnose diabetes (≥11.1 mmol/L), a threshold that can be associated with reduced pulmonary function [6]. Prospective studies are needed to confirm the association between glycemic excursions on CGM and clinical deterioration.…”
Section: To the Editormentioning
confidence: 99%
“…OGTT was performed according to international guidelines [17] and classified as described in previous studies [18]. The index proposed by Stumvoll et al, as well as insulin area under the curve, were used to evaluate insulin sensitivity and secretion, respectively [19].…”
Section: Oral Glucose Tolerance Testmentioning
confidence: 99%